Papermaking using Japanese method from aquatic macrophytes - Lau, Emmclan Sheng Hann (2012)
Eight (8) species of aquatic macrophytes; Eichhornia crassipes, Cyperus digitatus, Cyperus halpan, Cyperus sp., Limnocharis flava, Nelumbo nucifera, Nymphaea sp. and Scirpus grossus were explored for their usage as alternative source in papermaking. This study was conducted to determine the potential species and the suitable plant part as source in papermaking using Japanese papermaking method. The macrophytes were examined for fibre dimension and derived values for species selection. The stem part of C. digitatus, Cyperus sp. and S. grossus which have higher dry weight compared to leaf and root was used for paper production. The stem fibre was the most suitable part for papermaking compared to leaf fibre and petiole fibre. The stem of Cyperus sp., C. digitatus and S. grossus have highest slenderness ratio value of more than 60 which are 113.46, 105.54 and 99.05 respectively. The three selected macrophytes have unsatisfactory flexibility coefficient (<50) and Runkel ratio (>1). The stems chemical composition of C. digitatus and Cyperus sp. have higher content of cellulose compared to S. grossus with the value of 44.82%, 44.60% and 42.13%, respectively. The lignin content was lowest in Cyperus sp. which was 10.63% followed by C. digitatus (11.81%). and S. grossus (11.44%) The paper produced from C. digitatus has the highest value of tensile strength and breaking length of 2.61 kN/m and1.20, km respectively. The stems of the three selected macrophytes were suitable to produce moderate quality of paper using the Japanese papermaking method.